Gap prepulse inhibition and auditory brainstem-evoked potentials as objective measures for tinnitus in guinea pigs - Dehmel, Susanne; Eisinger, Daniel S.; Shore, Susan (Frontiers in Systems Neuroscience, 2012)
Tinnitus or ringing of the ears is a subjective phantom sensation necessitating behavioral models that objectively demonstrate the existence and quality of the tinnitus sensation. The gap detection test uses the acoustic startle response elicited by loud noise pulses and its gating or suppression by preceding sub-startling prepulses. Gaps in noise bands serve as prepulses, assuming that ongoing tinnitus masks the gap and results in impaired gap detection. This test has shown its reliability in rats, mice, and gerbils. No data exists for the guinea pig so far, although gap detection is similar across mammals and the acoustic startle response is a well-established tool in guinea pig studies of psychiatric disorders and in pharmacological studies. Here we investigated the startle behavior and prepulse inhibition (PPI) of the guinea pig and showed that guinea pigs have a reliable startle response that can be suppressed by 15 ms gaps embedded in narrow noise bands preceding the startle noise pulse. After recovery of auditory brainstem response (ABR) thresholds from a unilateral noise over-exposure centered at 7 kHz, guinea pigs showed diminished gap-induced reduction of the startle response in frequency bands between 8 and 18 kHz. This suggests the development of tinnitus in frequency regions that showed a temporary threshold shift (TTS) after noise over-exposure. Changes in discharge rate and synchrony, two neuronal correlates of tinnitus, should be reflected in altered ABR waveforms, which would be useful to objectively detect tinnitus and its localization to auditory brainstem structures. Therefore we analyzed latencies and amplitudes of the first five ABR waves at suprathreshold sound intensities and correlated ABR abnormalities with the results of the behavioral tinnitus testing. Early ABR wave amplitudes up to N3 were increased for animals with tinnitus possibly stemming from hyperactivity and hypersynchrony underlying the tinnitus percept.